A public development program for Thailand : report of a mission organized by the International Bank of Recoconstruction and Development at the request of the Government of Thailand - International Bank of Recoconstruction and Development; International Bank of Recoconstruction and Development; World Bank (Baltimore, Johns Hopkins Press, 1959)
The report aims to help government plan its contribution to the economic and social development of the country and to advise on the most effective ways pf fostering development.
Includes index
kjo 17/01/2019
Loans
Keywords: Economic policy; Social policy; Thailand